Perencanaan Sistem Pentanahan Tenaga Listrik Terintegrasi Pada Bangunan - Jamaaluddin Jamaaluddin; Sumarno Sumarno (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2017)
Terms of reliability and security is an absolute thing required in conducting the design of installation of Power System. To obtain the reliability and safety of the use of Power on the Building there must be a good interconnection between Lightning System (Lightning System), Grounding of existing electronic devices in buildings and Grounding System Grounding (Grounding System) it. The interconnection of the three systems is carried out on a Bar Plate located in the Control Room, with a good security indication value and a reliable system if at the point of Bar Plate located in the Control Room has a value below 1 Ω. Using the Dwight formula in obtaining the earthing resistance value of the Electrical Power System on clay as an example shows the depth of Copper Rod 1 m has a value of 0.72 Ω. So by doing a good interconnection between Lightning Trap System (Lightnig System), Grounding Electronic Devices and Grounding System Power (Grounding System) in a building will get a reliable and safe Power System Power.